Ingénierie, climatologie et topographie de l'être-dans-le-monde – Des îles pour penser l'architecture? - O. R. Meziou (Geographica Helvetica, 2019)
This text is an architect's reading of the last volume of Peter Sloterdijk's trilogy Ecumes (Foam), particularly the two chapters “Insulations” and “Indoors”. It raises the issue whether the atmospheric analysis that Sloterdijk develops from his representation of the being-in-the-world and the inhabitation can lead to a new understanding of space that would help reach more habitable future spaces. It suggests that the metaphor of the island can help construct some sort of an intermediary analysis and conception object: the (new) machine-to-live-in. Through the exercise of the atmospheric analysis, it suggests a new critical reading of the conception processes of human spatiality, which gives a glimpse into the possibility of setting new generators for contemporary space design.